Political Philosophy of Illumination: An Analysis of Political Dimensions in Suhrawardi's Thought - Reza Adeputra Tohis (Journal of Islamic Thought and Civilization, 2022)
Suhrawardi is a renowned philosopher famous for his thoughts on the philosophy of Illumination. His thoughts are contained in his mangnum opus, The Wisdom  of Al-Isryq (Hikmat Al-Isryq). This study aims to reveal the prominent aspect of various political dimensions in his work, whose primordial focus was on the aspects of the political system and the concept of power. The political system and the concept of power were then characterized as a political philosophy of Illumination. For this reason, this study not only uses a qualitative method with factual historical study techniques regarding figures but also uses an analytical approach to the theory of sociology of knowledge by Peter L. Berger and Thomas Lucmann and the theory of socio-political philosophy of al-Farabi's emanation. The sociology of knowledge is used to analyze the social dimensions involved in the formation of Suhrawardi's thoughts. Meanwhile, the socio-political philosophy of emanation is used to characterize the system and the concept of political power contained in the Wisdom of al-Isryq. The study concludes that the political system contained in the Illumination philosophy is divine, theocratic, and based on the concept of power in the form of self-control.Keywords: Hikmat al-Isryq, Illumination Political Philosophy, Suhrawardi, Reality, Sociology of Knowledge